f(-4)+f(3)=

Simple and best practice solution for f(-4)+f(3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(-4)+f(3)= equation:


Simplifying
f(-4) + f(3) = 0

Reorder the terms for easier multiplication:
-4f + f(3) = 0

Reorder the terms for easier multiplication:
-4f + 3f = 0

Combine like terms: -4f + 3f = -1f
-1f = 0

Solving
-1f = 0

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by '-1'.
f = 0

Simplifying
f = 0

See similar equations:

| 30u^5v^3x^6+24u^8v^9= | | (4-2i)(3+i)= | | r*2+2r+12=0 | | 5.6+x=8.4 | | 3(19/-23)=20(-19/-23)-7 | | 3(19/-23)=20(-19/23)-7 | | 16x-3x=3(2-x) | | (3x^7)(-5x^3)= | | 12=-7y | | Xa+xb=3c | | x^4-x^3-24x^2+37x+60=0 | | 7(-8c+9a)= | | -3(4m+7)= | | 12=-11y+4y | | (-7v-6)-(2v-4)= | | 6(2+15x)= | | 2/7-1/14 | | 32b-4+-2b-1= | | 10+5r=10-r | | (2/x)-x=(-23/5) | | (7/8)/m=(1/7) | | =(2a+3b-4c) | | 4+5-2=33 | | -2y+6+9y= | | 2/3-1/x=5/3x | | 3(n-4)=-15 | | X*.38=112 | | 26x^2-130x+6=0 | | 4x^2-y^2=11 | | 14j+3k= | | X^2+x+1=2 | | 8x+2z=4+7y |

Equations solver categories